VSPad : design and development of a memory training application for mobile phones. - Tan, Conrad Chee Hock. (2010)
Being a popular accessory, mobile phones provide an ideal delivery platform for personal memory training aids with use of keypad as a visuo-spatial input for better memory encoding. The objective of the project is to develop a memory training application (VSPad) for mobile phones using J2ME platform that caters to the Visual, Aural, Read/Write, Kinesthetic sensory preferences of learners and their memory limits. The VSPad System consists of a software application to be installed on each learner's mobile phone as well as a remote internet server acting as a cantral data repository. It is designed fr helping people remember lists of keywords better using their visual-spatial, kinesthetic, auditory strengths. A typical usage scenario begins when the user activates the VSPad mobile application for practicing the wordlists stored in it. Otherwise, the user can supply their own set of wordlists by editing and storing into the mobile storage using the application. The wordlists will be able to be organized into topics so the user is able to manage them within an account which can be uploaded to or downloaded from a remote server for sharing. A topic hierarchy can be formed with topics and sub-topics so as to associate the wordlists for better understanding and memorization.